ANALISA KINERJA GROUND STATION ADS-B (AUTOMATIC DIPENDENT SURVEILLANCE BROADCAST) DI PERUM LPPNPI CABANG DENPASAR - Endri Saputra, Novan (Politeknik Penerbangan Surabaya, 2024)
In 2001, the Federal Aviation Administration (FAA), the aviation industry and the Alaska community designed the Capstone project to improve aviation efficiency and safety. One of the new technologies being developed is the automatic dependent surveillance broadcast (ADS-B) monitoring system. After going through the research and development stage for several years, in 2005, the FAA stated that the ADS-B system was ready to be operated by the national general aviation system. Through the Capstone project, the FAA provides ground station equipment, avionics communications circuits, and datalinks that can be used by commercial flights. In early 2007, the FAA further intensified the deployment of the ADS-B system in a number of states in the United States. Apart from that, the FAA is also improving the quality of system access at remote airports. The ADS-B system works differently from the radar that is currently used by airports to detect the presence of aircraft. The ADS-B system uses Global Navigation Satellite System (GNSS) technology such as the Global Positioning System (GPS) installed on aircraft. The aircraft will transmit information such as speed, position, identification, aircraft height above sea level, and flight number to ground stations and other aircraft continuously. At the airport, this information is received by the air traffic control center to assist in piloting. The ADS-B system mechanism can run with the help of satellites which determine the aircraft's position based on the GNSS constellation.